Identification of mRNA features which facilitate their long-range transfer in an in vivo Drosophila model - Hill, CM (2021)
Extracellular vesicles (EV) are membrane bound carriers released by cells to mediate important aspects of intercellular communication; however, the basic principles of EV-biogenesis, in particular the mechanisms regulating mRNA EV-loading, are poorly characterised. Furthermore, a limited repertoire of tools has thus far made these processes challenging to research.